Hydrogen Line Shape Uncertainties in White Dwarf Model Atmospheres - Montgomery, M. H.; Dunlap, B. H.; Cho, P. B.; Gomez, T. A. (Frontiers in Astronomy and Space Sciences, 2022)
For isolated white dwarf (WD) stars, fits to their observed spectra provide the most precise estimates of their effective temperatures and surface gravities. Even so, recent studies have shown that systematic offsets exist between such spectroscopic parameter determinations and those based on broadband photometry. These large discrepancies (10% in effective temperature, 0.1 solar masses in mass) provide scientific motivation for reconsidering the atomic physics employed in the model atmospheres of these stars. Recent simulation work of ours suggests that the most important remaining uncertainties in simulation-based calculations of line shapes are the treatment of 1) the electric field distribution and 2) the occupation probability (OP) prescription. We review the work that has been done in these areas and outline possible avenues for progress.